2016
DOI: 10.1080/03019233.2016.1155841
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium oxide solubility in CaO–SiO2–VOXsystem

Abstract: The solubility of vanadium oxide in the SiO 2 -CaO-VO X system was investigated as a function of basicity (CaO/SiO 2 ) at a fixed temperature of 1600°C and oxygen partial pressure of 10 −10 atm. Formed phases and microstructures of saturated samples were identified with SEM-EDS analysis and XRD. Maximum solubility of vanadium oxide was between 15 and 20% independent of basicity. Pure karelianite (V 2 O 3 ) was formed in all samples at saturation of vanadium oxide. The morphology of karelianite changed with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…E. Åström et al determined the solubility limit of vanadium oxide in the CaO–SiO 2 –VO x system at 1873 K under the atmosphere of 97.7 volume pct CO and 2.3 volume pct CO 2 . They reported that the solubility limit varied in the range of 14 mass pct to 18 mass pct V 2 O 3 , which is comparable with the present results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. Åström et al determined the solubility limit of vanadium oxide in the CaO–SiO 2 –VO x system at 1873 K under the atmosphere of 97.7 volume pct CO and 2.3 volume pct CO 2 . They reported that the solubility limit varied in the range of 14 mass pct to 18 mass pct V 2 O 3 , which is comparable with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…The slags were equilibrated with a gas mixture of CO, CO 2 and Ar in Pt crucible, and the activity coefficient of V 2 O 3 was estimated also by assuming the existence of vanadium as V 3+ . In addition, the solubility of vanadium oxide in the CaO–SiO 2 –VO x system and in the CaO(30 and 35 mass %)‐Al 2 O 3 –SiO 2 –VO x system at 1873 K and the oxygen partial pressure of 10 −10 atm have been determined recently.…”
Section: Introductionmentioning
confidence: 99%
“…Relating to the preparation of some vanadium compounds and the pyrometallurgical extraction process of vanadium, CaO–SiO 2 –VO x is one of the most basic important systems . Hence, the phase equilibria and thermodynamic properties of this system are desirable in controlling the processes …”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, less attention was paid to the effects of oxygen partial pressure. For example, E. Astrom et al determined the effect of the ratio of CaO/SiO 2 on the saturation solubility of V 2 O 3 in the melts of CaO–SiO 2 –VO x system at 1873 K under the oxygen partial pressure of 10 −10 atm, but no investigations about the effect of oxygen partial pressure on the solubility of V 2 O 3 were reported. Tian et al measured the activity of VO in the CaO–SiO 2 –VO melts at 1773 K under the oxygen partial pressure of approximately 10 −16 atm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation